Influence of preloading-induced microcracking on the durability of concrete produced with different types of cement. (20th November 2018) - Venquiaruto, Simone; Bernardino da Silva, Lucília; Dal Molin, Denise C.C.
Highlights: Self-healing may contribute to reducing chloride penetration over time. Cement chemical composition can mitigate in different ways the effects of preloading. Pozzolanic reactions improve the effects of self-healing as curing ages increased. Remote sensing techniques are innovative approaches to the detection of microcracking. Abstract: As many concrete structures present premature degradation, large environmental and financial impacts are associated with repairing. It is essential, therefore, to understand mechanical and durability performance of concrete in different conditions of use. This study investigated the chloride penetration resistance of microcracked concretes after being exposed to early loading. So, cylindrical test specimens were prepared with two Brazilian cements, a high initial strength Portland cement and a pozzolanic one, with a water/cement ratio of 0.50. At the age of 3 days, some of the specimens were subjected to a load of 75% of their ultimate compressive strength while reference ones were not preloaded. All specimens were cured by immersion in water tanks for 3, 7, 28 and 91 days. After these periods, preloaded and reference specimens were tested in accordance with chloride penetration resistance (ASTM C1202/12). The best results were observed in the reference samples for both cement types. It was observed a significant reduction in chloride penetration for longer curing times in preloaded and reference specimens due to self-healing. Differences between preloaded and reference specimens were identified, at ages of 3 and 91 days, using scanning electron microscopy and electromagnetic radiation spectra, a non-destructive and low-cost remote sensing technique.